AKIBAT-AKIBAT HUKUM DARI PERISTIWA PERKAWINAN SIRRI - Adnani, Adriani (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
Official documents issued by the state are not the only shar'i evidence. The testimony of witnesses to the marriage or those who witnessed the marriage, are also valid and must be recognized by the state as shar'i evidence. The state may not stipulate that the only evidence to prove the validity of a person's marriage is a written document. This is because the Shari'a has determined the validity of other evidence other than written documents, such as witness testimony, oaths, confessions (iqrar), and so on. The consequences arising from the sirri marriage contract are greater the harm than the benefit. Settlement of problems caused by unregistered marriages can be resolved by submitting a request for a marriage determination (Isbat Nikah) in the Religious Court. Because of the many legal consequences of sirri marriages, awareness of the importance of registering marriages and legal awareness of marriages needs to be increased again